Earthquake/noise discrimination and estimation of P-S phases based on wave characteristics - Kokinou, E.; Panagiotakis, C.; Vallianatos, F. (Bulletin of the Geological Society of Greece, 2007)
Aim of the present work is to adapt and develop an algorithm for extracting first motion information from earthquake seismograms. In specifics, the present paper deals with the characterization of the ζ component of a given seismogram in order to discriminate an earthquake signal from noise recording. Segmentation and further classification of the seismogram comprises the initial step. The earthquake detection (P arrival) is performed using a low computation cost method based on signal energy. Furthermore, accurate picking of S arrival is based on signal energy and central frequency estimation. Experimental results show satisfied efficiency of the pre-mentioned scheme, low processing time and potential application in real-time environment